Diclofenac induced apoptosis via altering PI3K/Akt/MAPK signaling axis in HCT 116 more efficiently compared to SW480 colon cancer cells - Ergül, Zehragül; Bozdağ, Gülnihal; Ünsal, Zeynep Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; RENCÜZOĞULLARI, ÖZGE; COŞKUN, DENİZ (Springer Link, 2018)
Diclofenac is a preferential cyclooxygenase 2 inhibitor (COX-2) and member of non-steroidal anti-inflammatory drugs (NSAIDs). Inflammation is one of the main reason of poor prognosis of colon cancer cases; thereby NSAIDs are potential therapeutic agents in colon cancer therapy. In this study, our aim to understand the potential molecular targets of diclofenac, which may propose new therapeutic targets in HCT 116 (wt p53) and SW480 (mutant p53R273H) colon cancer cells. For this purpose, we identified different response against diclofenac treatment through expression profiles of PI3K/Akt/MAPK signaling axis. Our hypothesis was diclofenac-mediated apoptosis is associated with inhibition of PI3K/Akt/MAPK signaling axis. We found that sub-cytotoxic concentration of diclofenac (400 µM) promoted further apoptosis in HCT 116 cells compared to SW480 colon cancer cells. Diclofenac triggered dephosphorylation of PTEN, PDK, Akt, which led to inhibition of PI3K/Akt survival axis in HCT 116 colon cancer cells. However, diclofenac showed lesser effect in SW480 colon cancer cells. In addition, diclofenac further activated p44/42, p38 and SAPK/JNK in HCT 116 cells compared to SW480 cells.
Keywords: Diclofenac; NSAID; Colon cancer; Apoptosis